Processing Load Imposed by Line Breaks in English Temporal Wh-Questions - Hirotani, Masako; Terry, J. Michael; Sadato, Norihiro (Frontiers in Psychology, 2016)
Prosody plays an important role in online sentence processing both explicitly and implicitly. It has been shown that prosodically packaging together parts of a sentence that are interpreted together facilitates processing of the sentence. This applies not only to explicit prosody but also implicit prosody. The present work hypothesizes that a line break in a written text induces an implicit prosodic break, which, in turn, should result in a processing bias for interpreting English wh-questions. Two experiments – one self-paced reading study and one questionnaire study – are reported. Both supported the “line break” hypothesis mentioned above. The results of the self-paced reading experiment showed that unambiguous wh-questions were read faster when the location of line breaks (or frame breaks) matched the scope of a wh-phrase (main or embedded clause) than when they did not. The questionnaire tested sentences with an ambiguous wh-phrase, one that could attach either to the main or the embedded clause. These sentences were interpreted as attaching to the main clause more often than to the embedded clause when a line break appeared after the main verb, but not when it appeared after the embedded verb.